Using Therapeutic Prism Lenses in Children with Sensory Processing Disorder: A Case Study. - Nathu, Poonam (Optometry & Visual Performance, 2016)
Background: Sensory processing disorder (SPD), also known as sensory integration dysfunction, is a term that refers to the manner in which the nervous system processes information from the senses and responds via motor and behavioral outputs. Many daily tasks, such as eating, reading a book, or physical activities, require sensory integration processing. In order to assist with the communication of the sensory systems, therapeutic lenses can be used, allowing more accurate and efficient information processing. Case Report: An eight-year-old white male diagnosed with SPD, along with attention deficit hyperactivity disorder (ADHD), mood disorder, and separation anxiety, presented for an evaluation. The patient had presented with visual complaints and symptoms during deskwork. The patient was treated with 0.75Δ base in OU subsequent to indicators in our evaluation. Conclusion: After two months of wearing base in prism, the patient showed significant improvement in behavior, visual skills, and posture. This case underscores the importance of therapeutic prism and its effect on the involvement of SPD.